2018
DOI: 10.1080/17469899.2018.1520635
|View full text |Cite
|
Sign up to set email alerts
|

The importance of endoscopy in lacrimal surgery

Abstract: Introduction: The utilization of endoscopy in lacrimal surgeries has been increasing in the recent past with increasing indications. With the advent of newer generation of telescopes, the practice and learning of endoscopic lacrimal surgeries is expected to improve further. Areas covered: This review provides an overview about endoscope assistance in all conditions that involve pathologies of the lacrimal drainage apparatus. The authors have reviewed recently published literature on the techniques and outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Additionally, endoscopic instrumentation can be used post-operatively, thanks to the importance of direct visualization of the healing process. Surprisingly, it has been reported that nasal examination is not usually performed by most ophthalmologists, with potential consequences on treatment outcomes 15 . In the past, several authors have tried to identify the best clinical practice for lacrimal diseases, but no one has taken into account the role of multidisciplinary consultation between an ophthalmologist and otorhinolaryngologist in the management of lacrimal pathologies.…”
Section: S103mentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, endoscopic instrumentation can be used post-operatively, thanks to the importance of direct visualization of the healing process. Surprisingly, it has been reported that nasal examination is not usually performed by most ophthalmologists, with potential consequences on treatment outcomes 15 . In the past, several authors have tried to identify the best clinical practice for lacrimal diseases, but no one has taken into account the role of multidisciplinary consultation between an ophthalmologist and otorhinolaryngologist in the management of lacrimal pathologies.…”
Section: S103mentioning
confidence: 99%
“…Such an initial diagnostic step is a non-invasive, easy and low-cost way to establish an initial diagnosis, and if the result of this examination confirms a pathology of the eyelid, lacrimal gland, ocular bulb or meibomian gland, an otolaryngologist is not always required 16 . On the contrary, clinical examination of the nasal cavities by an otolaryngologist remains of major interest in case of both functional and obstructive lacrimal pathway pathologies 15 . In fact, even if in some lacrimal pathologies, like functional diseases, the available treatments are primarily performed by an ophthalmologist, the role of an otolaryngologist remain fundamental since he can provide an endoscopic assessment of the nasal fossa, excluding any form of influencing factors 15 .…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations